2012
DOI: 10.3109/14992027.2012.728724
|View full text |Cite
|
Sign up to set email alerts
|

A suggested model for decision-making regarding hearing conservation: Towards a systems theory approach

Abstract: From a systems theoretical approach it can be suggested that preventive strategies must consider more levels than just the individual, in order to achieve long lasting behavioural changes in adolescents' listening habits. To be able to get useful knowledge about preventive strategies, it is necessary to add context-specific variables into generic models such as TPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
51
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 20 publications
7
51
0
1
Order By: Relevance
“…[18] Previous research has revealed that the model of the theory of planned behavior might provide a theoretical framework to predict and alter human health behavior. [11] According to this model, by use of preventive campaigns, attitudes toward noise and HP can be altered resulting into an increase of HP use. [19] The authors would like to remark that the order of the intensity of music presentation in the present study might infl uence the opinion towards the sound levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Previous research has revealed that the model of the theory of planned behavior might provide a theoretical framework to predict and alter human health behavior. [11] According to this model, by use of preventive campaigns, attitudes toward noise and HP can be altered resulting into an increase of HP use. [19] The authors would like to remark that the order of the intensity of music presentation in the present study might infl uence the opinion towards the sound levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that attitudes toward noise and the use of HP play a role in the actual behavior of using HP in noise situations. [8,11] However, the use of HP is very low considering the high prevalence of noise-induced symptoms. Therefore, the second research part, conducted in February 2013, consisted of an online questionnaire assessing noise-induced symptoms, the attitudes toward more strict noise regulations, frequency of attendance at open air and indoor musical events, and the reasons why adolescents and young adults do (not) use HP in noisy situations.…”
Section: Introductionmentioning
confidence: 98%
“…One study by Keppler et al [34] found significantly worse hearing thresholds in young adults who considered that noise was not that risky or experienced more barriers against wearing HPDs. In the current study, the theoretical framework developed by Widén[35] was used to explain young people’s attitudes and behaviours towards leisure noise exposure. The model combines all the factors from the Theory of Planned Behaviour (TPB);[36] these are attitudes, subjective norms and perceived behavioural control, with the perceived benefits and barriers to modifying the behaviour and triggers to action from the Health Belief Model (HBM).…”
Section: Introductionmentioning
confidence: 99%
“…Rawool's [26] argumentation is somewhat in line with Widén, [27] that it is not merely enough to change adolescents attitudes and behaviors by adding, e.g. information or knowledge through some health educational program.…”
Section: Discussionmentioning
confidence: 91%